The challenges of digitalization and AI training of medical documentation specialists: a qualitative study of experiences in Augmedix Bangladesh - Talukder, Atqiya Maisha (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.